Flow Cytometry for Drug Discovery, Receptor Pharmacology and High Throughput Screening - Sklar, Larry A. (2007)
While flow cytometry is viewed as a mature technology, there have been dramatic advances in analysis capabilities, sorting, sample handling and sensitivity in the last decade. These advances contribute to its application for biological and chemical diversity, sample throughput, high content, and complex systems biology. This article will evaluate the new opportunities for flow cytometry relating to receptor assembly and pharmacology, as well as a range of screening applications.